Using interactive program-loyalty banners to reduce TV ad avoidance - Dix, Steve; Bellman, S.; Haddad, H.; Varan, D. (Advertsing Research Foundation, 2010)
This study used a sample of the general public in Australia to test whether program-related interactive banners superimposed over commercials in the break would reduce channel changing. Interaction with the banners reduced channel changes during the ad break by almost 40%, although interaction distracted viewers from optimally processing the ads. With the potential for advertising avoidance rates being driven up by DVRs, however, accepting reduced levels of advertising impact may be a necessary consequence of strategies designed to retain audiences, such as interactive loyalty banners.